Visualization of arrestin recruitment by a G Protein-Coupled Receptor - Shukla, Arun K. (2014)
G Protein Coupled Receptors (GPCRs) are critically regulated by β-arrestins (βarrs), which not only desensitize G protein signaling but also initiate a G protein independent wave of signaling(1-5). A recent surge of structural data on a number of GPCRs, including the β(2) adrenergic receptor (β(2)AR)-G protein complex, has provided novel insights into the structural basis of receptor activation(6-11). Lacking however has been complementary information on recruitment of βarrs to activated GPCRs primarily due to challenges in obtaining stable receptor-βarr complexes for structural studies. Here, we devised a strategy for forming and purifying a functional β(2)AR-βarr1 complex that allowed us to visualize its architecture by single particle negative stain electron microscopy (EM) and to characterize the interactions between β(2)AR and βarr1 using hydrogen-deuterium exchange mass spectrometry (HDXMS) and chemical cross-linking. EM 2D averages and 3D reconstructions reveal bimodal binding of βarr1 to the β(2)AR, involving two separate sets of interactions, one with the phosphorylated carboxy-terminus of the receptor and the other with its seven-transmembrane core. Areas of reduced HDX together with identification of cross-linked residues suggest engagement of the finger loop of βarr1 with the seven-transmembrane core of the receptor. In contrast, focal areas of increased HDX indicate regions of increased dynamics in both N and C domains of βarr1 when coupled to the β(2)AR. A molecular model of the β(2)AR-βarr signaling complex was made by docking activated βarr1 and β(2)AR crystal structures into the EM map densities with constraints provided by HDXMS and cross-linking, allowing us to obtain valuable insights into the overall architecture of a receptor-arrestin complex. The dynamic and structural information presented herein provides a framework for better understanding the basis of GPCR regulation by arrestins.